Developmental regulation of hepatitis B surface antigen expression in two lines of hepatitis B virus transgenic mice. - DeLoia, J A (1989)
Two lines of hepatitis B virus (HBV) transgenic mice, designated G7 and G26, show preferential expression of the 2.1-kilobase hepatitis B surface antigen (HBsAg) RNA transcript in liver and kidney tissues (R. D. Burk, J. A. DeLoia, M. K. ElAwady, and J. D. Gearhart, J. Virol 62:649-654, 1988). This transcript was first identified in transgenic mice at gestational day 14 and was detected at similar or increased levels through birth and early development. However, in contrast to 2.1-kilobase HBsAg mRNA levels, HBsAg protein levels in serum decreased shortly after birth. Thereafter, serum HBsAg increased 100-fold to adult levels, with a corresponding 5- to 10-fold increase in HBsAg mRNA levels. In addition, adult males have higher levels of HBsAg in serum than females. HBsAg in serum in males was reduced approximately 50% by surgical castration and was restored to near-normal levels by testosterone supplementation. Since both transgenic lines show similar patterns of gene expression, we suggest that HBsAg gene expression is determined by viral regulatory elements in response to host factors. Whether tissue specificity, developmental regulation, and sexual dimorphism of expression of the exogenous HBV sequences were determined by single or multiple HBV regulatory elements remains to be determined.